MICRO-DETERMINATION OF TADALAFIL IN PHARMACEUTICAL FORMULATIONS AND URINE SAMPLES OF DIABETIC PATIENTS TYPE-II IN TAIF AREA, SAUDIA ARABIA USING ATOMIC ABSORPTION AND ATOMIC EMISSION SPECTROMETRY - SABRY KH. MOHAMED; YOUSRI M. HUSSEIN; BASSEM M. RAAFAT (International Journal of Pharma and Bio Sciences, 2014)
New ion – associate complexes of tadalafil hydrochloride with [ Cadmium (II) and Zinc (II)] thiocyanates were precipitated and the excess unreacted metal complex was determined. A new method was given for the determination of tadalafil drug in pure solutions, in pharmaceutical formulations and urine samples of diabetic patients type – II using atomic emission and atomic absorption spectrometry. The drug can be determined by the affort method in the range 0.32 - 160.65 μg mL-1.